If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 32.7 = 2pi * r Multiply ip * r 32.7 = 2ipr Solving 32.7 = 2ipr Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2ipr' to each side of the equation. 32.7 + -2ipr = 2ipr + -2ipr Combine like terms: 2ipr + -2ipr = 0 32.7 + -2ipr = 0 Add '-32.7' to each side of the equation. 32.7 + -32.7 + -2ipr = 0 + -32.7 Combine like terms: 32.7 + -32.7 = 0.0 0.0 + -2ipr = 0 + -32.7 -2ipr = 0 + -32.7 Combine like terms: 0 + -32.7 = -32.7 -2ipr = -32.7 Divide each side by '-2pr'. i = 16.35p-1r-1 Simplifying i = 16.35p-1r-1
| 3r+20r-(-12)=-11 | | 2/6(4x-1) | | x+x(0.13)=1200 | | 1+x+-9=x-7 | | 5x+4(2)=-7(x-3) | | 2x/5-x-2/10=2 | | 24=-6(x-5) | | e^6x=64 | | 9/12-3/12 | | 3x^(2/3) | | 8=-4(v-20) | | 2x+log(9-x)=2 | | 7(x+7)+3=7x+6 | | 8x^2-2y=8 | | 9u=6/5 | | 6(2n+3)=91 | | 4n-14=2 | | W-16/2=1 | | 2-15n=-118 | | 1+1y= | | 0=-6 | | 6+(6-2)*6= | | -u^2+3u+18=0 | | -10p=-60 | | 4k-3k+4=13 | | -3/7z=-2/9 | | 7/p=0 | | 7/p-0 | | 11-2=75 | | -6y+5(-2y+3)=8-7(-7-y) | | -15=5q(3q-10)-5q | | 7x-3(5x-(5+x))=1-4x |